2013
DOI: 10.3389/fpsyg.2013.00631
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on neural systems of relational complexity

Abstract: Constructivist learning theory contends that we construct knowledge by experience and that environmental context influences learning. To explore this principle, we examined the cognitive process relational complexity (RC), defined as the number of visual dimensions considered during problem solving on a matrix reasoning task and a well-documented measure of mature reasoning capacity. We sought to determine how the visual environment influences RC by examining the influence of color and visual contrast on RC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…Indeed, analogy tasks are usually composed of 4 terms (A:B as C:D) [or sometimes 6 terms for visuospatial analogies; Geake and Hansen, 2010;Volle et al, 2010;Watson and Chatterjee, 2012], whereas matrix tasks usually display a 3-by-3 (or 3-by-2) matrix of terms. Thus, the greater visuospatial processing requirement in matrix problems could explain the additional recruitment of visuospatial regions and the attentional network [Kalbfleisch et al, 2013].…”
Section: Dissociable Visuospatial Analogy and Matrix Problem Task Netmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, analogy tasks are usually composed of 4 terms (A:B as C:D) [or sometimes 6 terms for visuospatial analogies; Geake and Hansen, 2010;Volle et al, 2010;Watson and Chatterjee, 2012], whereas matrix tasks usually display a 3-by-3 (or 3-by-2) matrix of terms. Thus, the greater visuospatial processing requirement in matrix problems could explain the additional recruitment of visuospatial regions and the attentional network [Kalbfleisch et al, 2013].…”
Section: Dissociable Visuospatial Analogy and Matrix Problem Task Netmentioning
confidence: 99%
“…The most frequently reported regions in these studies were the dorsolateral PFC [Christoff et al, ; Hampshire et al, ; Krawczyk et al, ; Kroger et al, ; Perfetti et al, ] sometimes extending to the rlPFC [Christoff et al, 2001; Golde et al, ; Hampshire et al, ; Krawczyk et al, 2011, see also Wendelken et al, ; Yamada et al, 2012], the premotor cortex [Golde et al, ; Kalbfleisch et al, ; Krawczyk et al, 2011; Perfetti et al, ; Yamada et al, ], and posterior parietal areas [Hampshire et al, ; Krawczyk et al, 2011; Perfetti et al, ]. Some studies have also shown the involvement of the lateral occipitotemporal regions [Hampshire et al, ; Kalbfleisch et al, ; Yamada et al, ], the anterior cingulate cortex [Kroger et al, ; Shokri‐Kojori et al, ], and the cerebellum [Kalbfleisch et al, ]. A recent and comprehensive review indicated that four‐term analogies and matrix problems might engage differentially the left and right rlPFC [Krawczyk, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation